2011
DOI: 10.1002/bjs.7682
|View full text |Cite
|
Sign up to set email alerts
|

Late results of endoscopic thoracic sympathectomy for hyperhidrosis and facial blushing

Abstract: ETS had an excellent and lasting effect on palmar hyperhidrosis. The effect on facial and axillary hyperhidrosis and facial blushing was less rewarding. The procedure regret rate increased over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 13 publications
1
32
0
3
Order By: Relevance
“…Another limitation of the use of ETS is the high rates of compensatory sweating observed postoperatively (range 8-95.4 %, mean 57.8 %). Compensatory sweating refers to increased sweating in non-denervated parts of the body [33]. With T2 sympathectomy, this commonly occurs on the back, trunk and lower limbs but can also manifest on other parts of the body.…”
Section: Surgical Managementmentioning
confidence: 99%
“…Another limitation of the use of ETS is the high rates of compensatory sweating observed postoperatively (range 8-95.4 %, mean 57.8 %). Compensatory sweating refers to increased sweating in non-denervated parts of the body [33]. With T2 sympathectomy, this commonly occurs on the back, trunk and lower limbs but can also manifest on other parts of the body.…”
Section: Surgical Managementmentioning
confidence: 99%
“…Median follow-up time with oxybutynin was 377 days (49-1,831 days). Most common CH sites were the back (n [ 8) and abdomen (n [ 5). After 6 weeks, the quality of life improved in 71.4% of patients.…”
mentioning
confidence: 99%
“…18 Indeed, there are investigations that indicated that the level of patient involvement in the decision making process is related to a reduction in patient's regret. 19,20,21,22,23,24,25 Indeed, the patient-surgeon relationship is based on trust but should not be seen as a contract. As Gregory and McCullough 26 expresses, the physician must understand patient's concerns.…”
Section: Decision Making Processmentioning
confidence: 99%